2018
DOI: 10.1212/wnl.0000000000004982
|View full text |Cite|
|
Sign up to set email alerts
|

Intravenous thrombolysis and platelet count

Abstract: Lower PC was associated with increased risk of sICH, while higher PC indicated increased mortality. Our data suggest that PC modifies outcome and complications in individual patients, while withholding IVT in all patients with PC < 100 × 10/L is challenged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 30 publications
1
41
0
2
Order By: Relevance
“…10,13 However, in patients treated with IVT, there aren’t enough studies to investigate the effect of PC on mortality, functional outcome, and risk of bleeding. In the study of Gensicke et al, 24 it was reported that as PC decreased, the risk of sICH increased, but the mortality and poor outcome decreased. We have seen in our study that the number of platelets is not related to the functional outcome.…”
Section: Discussionmentioning
confidence: 95%
“…10,13 However, in patients treated with IVT, there aren’t enough studies to investigate the effect of PC on mortality, functional outcome, and risk of bleeding. In the study of Gensicke et al, 24 it was reported that as PC decreased, the risk of sICH increased, but the mortality and poor outcome decreased. We have seen in our study that the number of platelets is not related to the functional outcome.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, rapid testing of the platelet count is a well-established standard in the treatment of stroke. Here, low platelet counts are excluded from tPA treatment due to the significantly increased risk of hemorrhagic transformation (HT) in platelet depleted patients (11). However, the question of whether and how platelet function contributes to tPA-associated HT has not been answered to date.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the enrolled patients in the registry, 21,592 were diagnosed with ischemic stroke or TIA and therein 16,842 patients with PC within a priori defined range of 100–400 × 10 9 /L were involved in the current analysis after excluding patients with pregnancy/within post-partum 6 weeks ( n = 3), sickle-cell disease ( n = 1), thrombocytopenia (8) (PC < 100 × 10 9 /L) ( n = 542), and thrombocytosis (9) (PC > 450 × 10 9 /L) ( n = 33), bleeding tendency/history caused by blood platelet disorders or coagulation factor deficiency ( n = 114), missing PC ( n = 1,703), and lost to 1 year follow-up ( n = 2,354).…”
Section: Methodsmentioning
confidence: 99%